Multimodal Media and Its Possible Application to Improve Reading and Writing of Students - Anggrainy, Septy (Universitas Islam Negeri Raden Intan Lampung, 2016)
In this 21st century, most of the students come from the digital environment. It makes the students learning change from only printed to screen pages. In order to improve students’ writing and reading litracies, teachers have to integrate technology into their English literacy classroom to make the students interested in learning English. In that classroom, the students will be exposed to multiple genres of texts and in the multimodal forms which combine words, images, and sounds as resources of learning. This paper describes how English literacy learning may be enhanced by using multimodal media. In teaching reading and writing, the teacher of English may use web-blogs, e-books e-journals, twitter, facebooks, e-mail in addition to printed texts.